PENENTUAN STANDAR ITIKAD BAIK DIREKSI ATAS KEBIJAKAN BISNIS YANG MENGALAMI KERUGIAN BERDASARKAN UNDANG-UNDANG NOMOR 40 TAHUN 2007 TENTANG PERSEROAN TERBATAS - ALFI SYAHRIN NASUTION (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Bismar2. Sunarmi3. T. Keizerina Devi A Good faith standard of a director of a limited liability company that suffersfinancial loss according to Article 95 paragraph (5) of UUPT (Law on LimitedLiability Company) is obscure and difficult to prove. In practice, this standard isinsufficient to prove a director’s guilt to relieve him from the liability for payingcompensation to the company according to the principles of Business Judgment Rule(BJR). This research discusses the standard of a director’s good faith in themanagement of a limited liability company which suffers financial loss according toUUPT, principles of BJR, and its relation to the implementation of the standard of adirector’s good faith in the case of two units of airplane i.e. Boeing 737-400 andBoeing 737-500 belonging to Lehman Brothers Ltd. rented by PT.MNA.This is a normative and prescriptive research. It provides argumentations andassessment whether it is right or wrong or concerning how the case of two units ofairplane i.e. Boeing 737-400 and Boeing 737-500 belonging to Lehman Brothers Ltd.rented by PT.MNA should be settled according to law.The standard of a company director’s good faith that suffers financial loss isassessed based on the elements in Article 97 paragraph (5) of UUPT. The fourelements are cumulative for one to another; one element requires the other elementsto be fulfilled in order to relieve the director from the liabilities for the company loss.The principle of BJR is to protect a director with good faith from unjusttreatment from the legal liabilities and charge for the loss incurred from the businessdecision that he makes. This principle is applicable for business decision andmanagement aspects (organization and/or management of the company).The implementation of the standard of a director’s good faith in makingdecision in business cannot only be grounded on Article 97 paragraph (5) of UUPT.Although some courts refer to the final results, some other courts refer to the process,yet in practice, a court generally refers to both. In addition to Article 97 paragraph(5) of UUPT, it also refers to the principles of custom in the articles of association,SOP (Standard of Procedure), and principles of GCG (Good Corporate Governance).The violation to either the articles of association or SOP is also considered aviolation to good faith. The plan of Hotasi DP Nababan to rent two units of airplaneand did not report it in RKAP (Work Plan and Company Budget) of 2006, is taken asan action done with bad faith by MA (the Supreme Court).It is expected that the judge be guided by Article 97 paragraph (5) of UUPT,articles of association, SOP, and principles of GCG; that the principle of BJR be onlyaddressed to the director with good faith and be in line with Article 97 paragraph (5)of UUPT, articles of association, SOP, and principles of GCG; and that the director’sgood faith at the court must not be applied to the company which gains profit frombusiness decisions, but it must also notice the violation to Article 97 paragraph(5) of UUPT, articles of association, SOP, and principles of GCG.Keywords: Standard of Good Faith, Directors, Business Decision, CompanyLoss, Business Judgment Rule